How Can We Know Each Other when We are So Different? Untangling the Complexity of Diverse Life Experience and Interconnection—A Model for Navigating the Paradox of Diversity to Create Empathic Learning Space - Elizabeth S Kasl; Lyle Yorks (Adult Education Research Conference, 2016)
We propose a model that describes how diversity, dialogue, emotion, and empathy interact in learning environments. The model provides guidance for addressing emotionally charged topics in highly diverse groups.
Keywords: paradox of diversity; empathic space; dialogue; emotional valence